Catering for Learner Diversity in Hong Kong Secondary Schools: Insights from the Relationships Between Students’ Learning Styles and Approaches - Hongbiao Yin; John Chi-Kin Lee; Zhonghua Zhang (ECNU Review of Education, 2020)
Purpose: Catering for learner diversity is a key issue in the recent educational reforms in Hong Kong. The present study addresses this issue through an investigation of the relationships between students’ learning styles and approaches to learning in Hong Kong secondary schools. Design/Approach/Methods: A total of 6,054 junior secondary students in Hong Kong responded to a questionnaire consisting of two instruments. A series of confirmatory factor analysis, two-way analysis of variance, and structural equation modeling analysis were conducted. Findings: The results identified three types of learning style among the students which are characterized by a cognitive orientation, a social orientation, and a methodological orientation. Some significant gender- and achievement-level differences were revealed. Compared with the socially oriented learning style, the cognitively and methodologically oriented learning styles were more extensively and strongly related to students’ approaches to learning, even though these students showed a greater preference for the socially oriented learning style. Originality/Value: It is unwise to blindly cater for students’ learning styles in classroom teaching and curriculum design. Teachers should adopt a comprehensive and balanced approach toward the design of curriculum and teaching which not only highlights the congruence between students’ learning styles and teacher’s pedagogy but also integrates the constructive frictions between them into classroom teaching.